2021
DOI: 10.1038/s41375-021-01276-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior JAK-inhibitor therapy with ruxolitinib on outcome after allogeneic hematopoietic stem cell transplantation for myelofibrosis: a study of the CMWP of EBMT

Abstract: JAK1/2 inhibitor ruxolitinib (RUX) is approved in patients with myelofibrosis but the impact of pretreatment with RUX on outcome after allogeneic hematopoietic stem cell transplantation (HSCT) remains to be determined. We evaluated the impact of RUX on outcome in 551 myelofibrosis patients who received HSCT without (n = 274) or with (n = 277) RUX pretreatment. The overall leukocyte engraftment on day 45 was 92% and significantly higher in RUX responsive patients than those who had no or lost response to RUX (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…In terms of pretreatment with ruxolitinib, multivariate analysis of a recent study on outcome of >500 patients with myelofibrosis showed that patients pretreated with ruxolitinib with ongoing spleen response at time of transplantation had a significantly lower risk of relapse (8% vs 19%) and better 2-year event-free survival (69% vs 54%) compared with patients without pretreatment. 36 In our cohort, 43% of patients with accelerated phase and 33% of patients with chronic phase received ruxolitinib before transplantation, and outcome for patients who received ruxolitinib pretreatment was similar with respect to overall survival as well as relapse incidence, whereas response data to ruxolitinib were not systematically available for this analysis. Moreover, no significant difference in 5-year nonrelapse mortality and relapse incidence was seen for ruxolitinib (25% and 18%) or no ruxolitinib pretreatment (31% and 16%), respectively.…”
Section: Discussionmentioning
confidence: 92%
“…In terms of pretreatment with ruxolitinib, multivariate analysis of a recent study on outcome of >500 patients with myelofibrosis showed that patients pretreated with ruxolitinib with ongoing spleen response at time of transplantation had a significantly lower risk of relapse (8% vs 19%) and better 2-year event-free survival (69% vs 54%) compared with patients without pretreatment. 36 In our cohort, 43% of patients with accelerated phase and 33% of patients with chronic phase received ruxolitinib before transplantation, and outcome for patients who received ruxolitinib pretreatment was similar with respect to overall survival as well as relapse incidence, whereas response data to ruxolitinib were not systematically available for this analysis. Moreover, no significant difference in 5-year nonrelapse mortality and relapse incidence was seen for ruxolitinib (25% and 18%) or no ruxolitinib pretreatment (31% and 16%), respectively.…”
Section: Discussionmentioning
confidence: 92%
“…The optimal timing for ruxolitinib discontinuation before HSCT is not well defined. However, several retrospective studies have demonstrated a better prognosis in MF patients responsive to pretreatment with ruxolitinib before HSCT, with a significantly lower risk of relapse and faster engraftment than in patients without ruxolitinib pretreatment [ 23 , 24 ]. In our survey, more than 60% of physicians stated that they would discontinue ruxolitinib the day before starting the conditioning regime for HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Both ruxolitinib and fedratinib are classified as type-I JAK inhibitors, competitively binding within the ATP-binding site of JAK2 in the active (DFG-in) conformation ( Figure 3A ) ( Leroy and Constantinescu, 2017 ). Ruxolitinib therapy can limit further bone marrow fibrosis in JAK2 p. V617F-driven MF and PV ( Verstovsek et al, 2017b ; Kroger et al, 2021 ) and multiple studies have shown that ruxolitinib therapy correlates with improved overall survival ( Verstovsek et al, 2012a ; Vannucchi et al, 2015a ; Bose and Verstovsek, 2020 ; Kroger et al, 2021 ). However, the significance of this survival benefit is debated due to statistical limitations of the pioneer COMFORT-1 (NCT00952289) and COMFORT-2 (NCT00934544) trials ( Passamonti et al, 2015 ; Cervantes and Pereira, 2017 ).…”
Section: Jak2 As a Target For Precision Medicine In Allmentioning
confidence: 99%